PENGARUH KOMPETENSI PROFESIONAL GURU DAN MINAT BELAJAR TERHADAP HASIL BELAJAR SISWA MELALUI MOTIVASI BELAJAR SEBAGAI VARIABEL INTERRVENING PADA MATA PELAJARAN EKONOMI - Rahayu, Tri; Thomas, Partono (Universitas Negeri Semarang, 2017)
The purpose of this research is to find out whether is there any influence of professional competence of teacher and learning interest toward students’ learning outcomes either directly or indirectly through learning motivation as intervening variable. The population in this research are 149 students of grade XI social science of SMA N 2 Ungaran. Sample used were 109 students, taken with proportional random sampling technique. Methods of data collection using the questionnaire and documentation. Methods of data analysis using desciptive statistical analysis and path analysis. The result showed that (1) there was a simultaneously influence of professional competence of teacher, learning interest, and learning motivation toward students’ learning outcomes of 64,1%., meanwhile the partial influence was 11,56% for professional competence of teacher, 5,76% for learning interest, and learning motivation was 22,18%., (2) there was an influence of professional competence of teacher toward students’ learning outcomes through learning motivation of 10,83%, and influence of learning interest toward students’ learning outcomes through learning motivation was 19,44%. According to the research, it can be concluded that professional competence of teacher and learning interest influences students’ learning outcomes both directly and indirectly through learning motivation.